ICTAC Kinetics Committee recommendations for analysis of thermal polymerization kinetics - Vyazovkin, Sergey; Achilias, Dimitris; Fernandez-Francos, Xavier; Galukhin, Andrey; Sbirrazzuoli, Nicolas (Thermochimica acta, 2022)
•Recommendations are provided for kinetic analysis of thermal polymerization.•Main focus is on analysis of DSC measurements.•Multi-step nature of polymerization kinetics is emphasized.•Model-fitting, isoconversional, and deconvolution analyses are discussed.•Specific advices are offered for efficient usage of each analysis. The present recommendations have been developed by the Kinetics Committee of the International Confederation for Thermal Analysis and Calorimetry (ICTAC). The recommendations provide guidance on kinetic analysis of thermal polymerization, which incorporates both linear and crosslinking polymerization (curing). The focus is on treating the kinetics as measured by differential scanning calorimetry (DSC). The recommendations discuss basic reaction mechanisms and emphasize the multi-step nature of the polymerization kinetics. An overview of mechanistic and phenomenological models is provided for polymerization controlled by reaction kinetics and diffusion. Three different approaches to evaluation of kinetic parameters (activation energy, preexponential factor, reaction model) for individual steps are considered. These approaches comprise model-fitting, isoconversional, and deconvolution analyses. Practical advices are offered for effective usage of each approach. Attention is paid to the typical problems and to the ways of addressing them. The recommendations are intended to assist with efficiently conducting kinetic analysis and interpreting its results.